Мова в Україні: стан, функції, перспективи - Радчук, В.Д. (Мовознавство, 2002)
Стаття порушує проблему окремішності мови на підставі очевидних і визнаних світовою практикою критеріїв, зокрема обсягe лексичних збігів та відмінностей, чим спростовує зашореність псевдостатистики щодо поділу українського суспільства на вживані ним буцімто тільки дві панівні мови. Як конкурентні розрізняє п’ять поширених сьогодні й тому доволі стійких комунікативних систем — знарядь порозуміння, тобто в проекції на майбутнє — п’ять варіантів розвитку мовної ситуації в Україні. The article focuses on the problem of separability of a language, its disjuncture, entity and integrity as viewed through the criteria that are obvious and universally acknowledged, in particular through the amount of lexical units that coincide or differ in translations. This refutes statistical data on the two dominant tongues used in Ukraine and removes blinkers of bias from social stratification. As for Ukraine, the author distinguishes five fairly stable rivals among the current communicative systems and foresees five corresponding variants of language development on the terrain.